Prioritization of maternal and newborn health policies and their implementation in the eastern conflict affected areas of the Democratic Republic of Congo: a political economy analysis - Rosine Nshobole Bigirinama; Mamothena Carol Mothupi; Pacifique Lyabayungu Mwene-Batu; Naoko Kozuki; Christian Zalinga Chiribagula; Christine Murhim’alika Chimanuka; Gaylord Amani Ngaboyeka; Ghislain Balaluka Bisimwa (Health Research Policy and Systems, 2024)
Abstract Background Maternal and neonatal mortality remains a major concern in the Democratic Republic of Congo (DRC), and the country’s protracted crisis context exacerbates the problem. This political economy analysis examines the maternal and newborn health (MNH) prioritization in the DRC, focussing specifically on the conflict-affected regions of North and South Kivu. The aim is to understand the factors that facilitate or hinder the prioritization of MNH policy development and implementation by the Congolese government and other key actors at national level and in the provinces of North and South Kivu. Methods Using a health policy triangle framework, data collection consisted of in-depth interviews with key actors at different levels of the health system, combined with a desk review. Qualitative data were analysed using inductive and then deductive approaches, exploring the content, process, actor dynamics, contextual factors and gender-related factors influencing MNH policy development and implementation. Results The study highlighted the challenges of prioritizing policies in the face of competing health and security emergencies, limited resources and governance issues. The universal health coverage policy seems to offer hope for improving access to MNH services. Results also revealed the importance of international partnerships and global financial mechanisms in the development of MNH strategies. They reveal huge gender disparities in the MNH sector at all levels, and the need to consider cultural factors that can positively or negatively impact the success of MNH policies in crisis zones. Conclusions MNH is a high priority in DRC, yet implementation faces hurdles due to financial constraints, political influences, conflicts and gender disparities. Addressing these challenges requires tailored community-based strategies, political engagement, support for health personnel and empowerment of women in crisis areas for better MNH outcomes.